15-17 May 2024, 16th Global Communication Association Conference “The Future(s) of Communication: Promises and Predicaments” - Büşra Tosun Durmuş (Türkiye İletişim Araştırmaları Dergisi)
The 16th Global Communication Association Conference was held between May 15-17, 2024, hosted by Marmara University, to address the interdisciplinary nature of communication studies and the challenges of the 21st century. Under the theme "The Future of Communication: Promises and Predicaments," the conference covered topics such as digitalization, artificial intelligence, media psychology, societal sustainability, and crisis communication. With participants from 15 countries, the event highlighted critical issues including data security, disinformation, media ethics, and the societal impacts of emerging communication technologies. Emphasizing Türkiye's proactive role in global communication, the conference provided a platform for developing innovative and inclusive approaches to addressing global communication challenges.